1992
DOI: 10.2307/2010488
|View full text |Cite
|
Sign up to set email alerts
|

Peace Between Participatory Polities: A Cross-Cultural Test of the “Democracies Rarely Fight Each Other” Hypothesis

Abstract: Evidence is accumulating that, in the modern international system, democracies rarely fight each other. But the reasons for the phenomenon are not well understood. This article explores a similar phenomenon in other societies, using cross-cultural ethnographic evidence. It finds that polities organized according to more participatory (“democratic”) principles fight each other less often than do polities organized according to hierarchical principles. Stable participatory institutions seem to promote peaceful r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
1
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(63 citation statements)
references
References 25 publications
1
60
1
1
Order By: Relevance
“…Although the theoretical literature is far from in agreement about the effect of democracy on conflict (e.g., contrast Waltz, 1959with Doyle, 1986, the empirical results, with few exceptions, do support the proposition that democracy reduces interstate conflict (Babst, 1972;Bremer, 1992a;Chan, 1984;Dixon, 1989;Ember, Ember, Russett, 1992;Maoz and Abdolali, 1989;Morgan and Campbell, 1991;Morgan and Schwebach, 1991;Ray, 1992;Rummel, 1983;Russett and Antholis, 1991;Small and Singer, 1976).…”
Section: Democracymentioning
confidence: 92%
See 1 more Smart Citation
“…Although the theoretical literature is far from in agreement about the effect of democracy on conflict (e.g., contrast Waltz, 1959with Doyle, 1986, the empirical results, with few exceptions, do support the proposition that democracy reduces interstate conflict (Babst, 1972;Bremer, 1992a;Chan, 1984;Dixon, 1989;Ember, Ember, Russett, 1992;Maoz and Abdolali, 1989;Morgan and Campbell, 1991;Morgan and Schwebach, 1991;Ray, 1992;Rummel, 1983;Russett and Antholis, 1991;Small and Singer, 1976).…”
Section: Democracymentioning
confidence: 92%
“…Numerous studies (Babst, 1972;Chan, 1984;Dixon, 1989;Ember, Ember, and Russett, 1992;Maoz and Abdolali, 1989;Morgan and Campbell, 1991;Morgan and Schwebach, 1991;Ray, 1992;Rummel, 1983;Russett and Antholis, 1991;Small and Singer, 1976), employing a variety of approaches, methods, and indicators of democracy have found the war-inhibiting effects of democracy. Some have seized upon this finding with religious fervor and trumpeted to the world that if all states were democratic, war would cease to plague mankind.…”
Section: Introductionmentioning
confidence: 99%
“…These studies include Moaz and Abdolali (1989), Levy (1989), Morgan and Campbell (1991), Morgan and Schwebach (1991), Siverson and Emmons (1991), Ray (1992), Ember et al (1992), Bremer (1992aBremer ( , 1992b, Russett and Antholis (1992), Moaz and Russett (1993), Bremer (1993), and Farber and Gowa (1994). Noteworthy among these studies is the consistency of the findings; so much so that Levy (1989, p. 270) called the "democracies rarely fight" phenomena a "law," and Bremer indicated that a panel of leading political scientists "gave unanimous support to the proposition" (Bremer, 1992b, p. 1).…”
Section: Introductionmentioning
confidence: 99%
“…67. See Ember, Ember, andRussett 1992;and Russett 1993, chap. 5. these institutional effects by contrasting the warlike Marshallese Islanders, who were ruled by a stratified hereditary elite with absolute life-and-death powers over their subjects, to the peaceful Cuna Indians of Panama, whose elected chiefs could be sacked at any time by popular demand.…”
Section: Institutional Hypothesesmentioning
confidence: 99%